2017
DOI: 10.1097/mpg.0000000000001587
|View full text |Cite
|
Sign up to set email alerts
|

Primary Budd‐Chiari Syndrome in Children

Abstract: Primary Budd-Chiari syndrome is a rare cause of liver disease in children in the western world. Here we present a retrospective review of children with Primary Budd-Chiari syndrome presenting from January 2001 to November 2015 to our hospital. Seven children were identified. Their presentation was mostly chronic. All had predisposing factors for thrombosis and were started on anticoagulation. Radiological interventions (2 transjugular intrahepatic portosystemic shunts and 1 hepatic vein stenting), liver transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…The histological features were, however, similar to what are documented 26 . Even though pediatric case series of BCS have been documented across continents, yet reports of children with hepatic presentations of Niemaan‐Pick Disease are quite scant from Asia‐Pacific region 27–29 …”
Section: Discussionsupporting
confidence: 58%
“…The histological features were, however, similar to what are documented 26 . Even though pediatric case series of BCS have been documented across continents, yet reports of children with hepatic presentations of Niemaan‐Pick Disease are quite scant from Asia‐Pacific region 27–29 …”
Section: Discussionsupporting
confidence: 58%
“…The management decision depends on several factors including local expertise, presentation of patient, site of blockage and structural anatomy. In the present era, most of the BCS are managed with radiological intervention [28], however, the risk of endothelial damage and the of a new thrombosis was a limitation for this therapeutic option in our patient. Prothrombotic states need to be worked up carefully.…”
Section: Normal Valuesmentioning
confidence: 83%
“…Nobre et al (18) have reported on a case series of 7 children with BCS from the UK, which included 2 liver transplants and 1 meso-caval shunt. No surgical shunts or transplants for chronic liver disease were performed in this series.…”
Section: Discussionmentioning
confidence: 99%